A quick-responding technique for parameters of turning maneuver. (1st May 2019) - Duman, S.; Bal, S.
Abstract: A novel and fast technique is proposed to predict the parameters of turning maneuvering performance of a surface combatant at mid and high Froude numbers. An empirical model with two parameters (ship advance speed and rudder angle) and three unknown coefficients is introduced. First, resistance of rudder appended hull has been computed by the time-dependent straight-ahead towing simulations. The code has been verified by implementing three different solution verification methods; Grid Convergence Index (GCI), Correction Factor (CF) and Factors of Safety (FS). After this, Direct Maneuvering Simulations (DMS) have been performed by implementing overset grid technique. Singular body forces located at the same position and direction with the propellers have been applied to the vessel for propulsion during DMS. The method has been validated by comparing the results of bare hull straight-ahead towing case and δ = 35° turning circle simulation ones with the available experimental data. The numerical results have then been used to calculate the unknown coefficients by linear regression analysis. It has been found that the proposed CFD-based empirical model is reliable and robust for both interpolated and extrapolated cases as well as the test matrix with reasonable accuracy and also applicable to similar surface ships. Highlights: A novel and quick method is presented to obtain the turning circle parameters of ships at medium and relatively high Froude numbers. The turning manoeuvre has been simulated using overset grid technique with relatively coarse grid. The numerical simulation results have been verified using the latest solution verification methods and have been validated. A new empirical method, which is based on rudder angle and ship advance speed, has been developed.